Analisis Efisiensi dan Efektifitas Pengelolaan Keuangan Daerah Kota Sorong - Jumame, Linda (Universitas Sam Ratulangi, 2018)
Sorong is an autonomous city in the province of west Papua. The source of income of the city of Sorong is mainly from services. Since is does not have enough natural resource to manage.Therefore the local government of the city of Sorong must be sensitive in managingÂ its finance in order to achieve efficiency and effectiveness. Based on the recent five years data, the efficiency managing the government finance most significant in the year 2013 and 2014. The revenue and spending in the 2012 and 2013 tended to slow down.Keywords: Â efficiency, effectiveness, local government, Sorong